Carbon negative electrode material, preparation method thereof and sodium ion battery

By carbon coating and high-temperature carbonization of anthracite, carbon negative electrode materials with high first-time Coulomb efficiency and good cycle stability were prepared, which solved the problem of low cycle stability of sodium ion battery materials and improved the energy density of the battery and security.

CN119490175AActive Publication Date: 2025-02-21LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411613427.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The circulation stability of existing sodium ion battery materials is not high, and the stability of the electrolyte also needs to be further improved, resulting in challenges in energy density and safety of sodium ion batteries.

Method used

Anthracite is used as the precursor, carbon coating is carried out through chemical vapor deposition of carbon-hydrocarbon gases, and then carbon anode material is prepared by high-temperature carbonization. The method includes steps such as decomposition treatment, grinding, carbon coating and high-temperature carbonization, simplifying raw material and process conditions and reducing production costs.

Benefits of technology

It improves the first Coulomb efficiency of carbon anode materials, enhances the cyclic stability and electrochemical properties of the materials, and is suitable for negative electrode materials for sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132624560000091
    Figure BDA0005132624560000091
  • Figure HDA0005132624760000011
    Figure HDA0005132624760000011
  • Figure HDA0005132624760000012
    Figure HDA0005132624760000012
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a carbon negative electrode material, a preparation method thereof and a sodium ion battery. Compared with the prior art, the coal-based hard carbon is prepared by adopting secondary carbonization, the anthracite is used as a precursor, different coating carbon sources are introduced to carry out carbon coating on the anthracite, then a carbon deposition process is carried out, and finally high-temperature carbonization is carried out to obtain the carbon negative electrode material. The preparation method provided by the invention has the advantages of few raw materials and reagents, easy control of conditions in the synthesis process, simple operation, low temperature, less energy consumption, high yield and easy industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] The development of renewable energy and large-scale energy storage systems is seen as an effective way to solve the current energy crisis. Although lithium-ion batteries have been proven in many fields such as automobiles and portable electronic devices, the uneven distribution of lithium mineral resources has caused major constraints on large-scale stationary energy storage. As an alternative, sodium-ion batteries have attracted increasing attention due to their cost-effectiveness and similar chemical properties to lithium. Sodium-ion batteries are a new type of rechargeable battery that can complement some areas of lithium-ion batteries. Sodium is an abundant element in the earth's crust. Compared with lithium, it is more widely distributed and cheaper, so sodium-ion batteries have greater resource sustainability and economy. In addition, sodium-ion batteries have huge energy density and are expected to meet the growth of future energy demand. Therefore, sodium-ion batteries are considered to be an energy storage technology with great development potential. However, sodium-ion batteries still face challenges in terms of cycle life, energy density, safety, etc. The existing sodium-ion battery materials have low cycle stability, and the stability of the electrolyte also needs to be further improved. Therefore, the research focus of sodium-ion batteries is mainly on material design, electrolyte optimization, interface engineering, etc., to improve their cycle stability and energy density, and further promote their commercial application.

[0003] Carbon materials are currently the main negative electrode materials for sodium ion batteries due to their abundant sources and low cost. Among them, hard carbon has a large interlayer spacing and a large number of lattice defects, which can make more Na + It can be inserted into the carbon layer, so it has attracted much attention. Polymers, resins and carbon-containing compounds are often used as precursors of hard carbon because they can provide high sodium storage capacity, which has attracted the interest of researchers. However, since sodium ions will be consumed at the defects of the material to form a stable solid electrolyte interface (SEI) film, this often sacrifices the initial Coulombic efficiency (ICE). Therefore, it becomes particularly important to develop low-cost, high ICE and high-capacity hard carbon. Anthracite has the advantages of abundant resources, low cost, high carbon yield and low impurity content, and is a promising carbon material precursor. But unfortunately, anthracite-derived carbon usually has abundant surface defects, which greatly affects ICE.

[0004] In order to optimize and adjust the microstructure and pore structure of hard carbon materials, a Chinese patent with publication number CN112645305A discloses a method for preparing anthracite-based hard carbon material by combining pre-activation pore formation with high-temperature carbonization, comprising the following steps: (1) grinding and selection: crushing and screening the raw coal to obtain powder of target particle size; (2) pre-activation: mixing the activation gas or activator with the powder, heating the mixture to 700-1000°C at a heating rate of 2-20°C / min under the protection of an inert atmosphere, and keeping the mixture at that temperature for 1-6 hours to obtain a pre-activated product; (3) carbonization: heating the pre-activated product to 800-1800°C at a heating rate of 2-20°C / min under the protection of an inert atmosphere, and keeping the mixture at that temperature for 0.5-10 hours to obtain anthracite-based hard carbon material. When hard carbon materials are used as negative electrodes for sodium ion batteries, the reversible capacity is 154.7 mAh / g at 0.1C (1C = 300 mA / g) and the first coulombic efficiency is 73%, but the preparation method is complicated and the electrochemical performance obtained still needs to be improved. Therefore, the research on hard carbon negative electrodes for sodium ion batteries has gained more and more attention from domestic and foreign researchers and the industry, and it is urgent to explore an efficient sodium ion negative electrode material. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a carbon negative electrode material and a preparation method thereof, and a sodium ion battery. The carbon material has a high first coulombic efficiency as a negative electrode material for a sodium ion battery.

[0006] The present invention provides a method for preparing a carbon material, comprising the following steps:

[0007] S1) subjecting anthracite to a de-impurity treatment to obtain anthracite free of impurities;

[0008] S2) grinding the anthracite from which impurities have been removed to obtain ground anthracite;

[0009] S3) introducing hydrocarbon gas into the ground anthracite in a protective atmosphere to perform carbon coating by chemical vapor deposition to obtain carbon-coated coal powder;

[0010] S4) carbonizing the carbon-coated coal powder at high temperature in a protective atmosphere to obtain a carbon material.

[0011] Preferably, an organic carbon source is added during grinding in step S2), and then pyrolysis is performed to obtain ground anthracite.

[0012] Preferably, the mass ratio of the anthracite from which impurities have been removed to the organic carbon source is 20:(0.5-2).

[0013] Preferably, the anthracite is selected from No. 3 anthracite;

[0014] The organic carbon source is selected from one or more of asphalt, phenolic resin and cellulose;

[0015] And / or, the protective atmosphere is selected from one or more of argon, helium, neon, krypton, xenon and radon;

[0016] And / or, the hydrocarbon gas is selected from one or more of methane, acetylene, ethylene, propane and natural gas.

[0017] Preferably, the pyrolysis temperature in step S2) is 400°C to 500°C; the pyrolysis time is 1 to 3 hours; and the heating rate of the pyrolysis is 1 to 10°C / min.

[0018] Preferably, the temperature of the carbon coating in step S3) is 400°C to 500°C; the time of the carbon coating is 1 to 3 hours; and the heating rate of the carbon coating is 3 to 7°C / min.

[0019] Preferably, the volume ratio of the protective atmosphere to the hydrocarbon gas is 5:(0.5-2); the flow rate of the hydrocarbon gas is 150-250 mL / min.

[0020] Preferably, the temperature of the high-temperature carbonization in step S4) is 1000°C to 1500°C; the time of the high-temperature carbonization is 1 to 3 hours; and the heating rate of the high-temperature carbonization is 1 to 10°C / min.

[0021] The present invention also provides a negative electrode material for a sodium ion battery, comprising the carbon material prepared by the above preparation method.

[0022] The present invention also provides a sodium ion battery, comprising the above-mentioned negative electrode material for a sodium ion battery.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1) The present invention adopts secondary carbonization to prepare coal-based hard carbon, using anthracite as a precursor, introducing different coating carbon sources to carbon-coat the anthracite, then undergoing a carbon deposition process, and finally high-temperature carbonization to obtain a carbon negative electrode material;

[0025] 2) The preparation method of the present invention has few raw materials and reagents, the synthesis process conditions are easy to control, the operation is simple, the temperature is low, the energy consumption is low, the yield is high, and it is easy to industrialize production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the carbon material obtained in Example 1 of the present invention;

[0027] Figure 2 is the XRD pattern of the carbon material obtained in Example 1 of the present invention;

[0028] Figure 3 This is a cycle performance diagram of the carbon material obtained in Example 1 of the present invention;

[0029] Figure 4 This is a cycle performance diagram of the carbon material obtained in Example 2 of the present invention;

[0030] Figure 5 This is a cycle performance diagram of the carbon material obtained in Example 3 of the present invention;

[0031] Figure 6 This is a cycle performance diagram of the carbon material obtained in Example 4 of the present invention;

[0032] Figure 7 This is a cycle performance diagram of the carbon material obtained in Comparative Example 1 of the present invention;

[0033] Figure 8 This is a cycle performance diagram of the carbon material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] The present invention provides a method for preparing a carbon material, comprising the following steps: S1) subjecting anthracite to impurity removal treatment to obtain anthracite from which impurities have been removed; S2) grinding the anthracite from which impurities have been removed to obtain ground anthracite; S3) introducing a carbon hydrocarbon gas into the ground anthracite in a protective atmosphere to perform carbon coating by chemical vapor deposition to obtain carbon-coated coal powder; S4) carbonizing the carbon-coated coal powder at high temperature in a protective atmosphere to obtain a carbon material.

[0036] The present invention has no particular limitation on the sources of all raw materials.

[0037] The anthracite is subjected to a de-impurity treatment to obtain anthracite with impurities removed; the anthracite can be anthracite well known to those skilled in the art without any special restrictions, and is preferably No. 3 anthracite in the present invention; the de-impurity treatment can be carried out by a method well known to those skilled in the art without any special restrictions, and in the present invention, the de-impurity treatment is preferably carried out by a mixed solution of hydrochloric acid and hydrofluoric acid; the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and hydrofluoric acid is preferably 3-6 mol / L, more preferably 4-5 mol / L; the mass concentration of hydrofluoric acid in the mixed solution of hydrochloric acid and hydrofluoric acid is preferably 5%-15%, more preferably 8%-12%, and even more preferably 10%; after the de-impurity treatment, it is preferably washed repeatedly with deionized water to obtain anthracite with impurities removed.

[0038] In a specific embodiment provided by the present invention, the anthracite from which impurities have been removed is ground to obtain ground anthracite; the grinding method is preferably ball milling; the grinding time is preferably 10 to 30 hours, more preferably 15 to 25 hours, and even more preferably 20 hours; the particle size of the ground anthracite is preferably less than or equal to 500 mesh.

[0039] In another specific embodiment provided by the present invention, an organic carbon source is added during grinding, and then pyrolysis is performed to obtain ground anthracite; the mass ratio of the anthracite from which impurities have been removed to the organic carbon source is preferably 20:(0.5-2), more preferably 20:(0.5-1.5), further preferably 20:(0.8-1.2), and most preferably 20:1; the organic carbon source can be an organic carbon source well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of asphalt, phenolic resin and cellulose; the asphalt is preferably coal tar asphalt ; The grinding method is preferably ball milling; the grinding time is preferably 10 to 30 hours, more preferably 15 to 25 hours, and more preferably 20 hours; the anthracite with impurities removed and the organic carbon source are ground to a particle size preferably less than or equal to 500 mesh; the pyrolysis temperature is preferably 400°C to 500°C, more preferably 420°C to 480°C, more preferably 440°C to 460°C, and most preferably 450°C; the pyrolysis time is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and more preferably 2 hours; the heating rate of the pyrolysis is preferably 1 to 10°C / min.

[0040] The ground anthracite is carbon-coated by introducing hydrocarbon gas in a protective atmosphere by chemical vapor deposition to obtain carbon-coated coal powder; the protective atmosphere can be any protective atmosphere well known to those skilled in the art without any special limitation, and in the present invention, it is preferably one or more of argon, helium, neon, krypton, xenon and radon; the hydrocarbon gas is preferably one or more of methane, acetylene, ethylene, propane and natural gas; the volume ratio of the protective atmosphere to the hydrocarbon gas is preferably 5: (0.5-2); The flow rate of the hydrocarbon gas is preferably 150-250 mL / min, more preferably 180-220 mL / min, and more preferably 200 mL / min; the temperature of the carbon coating is preferably 400°C-500°C, more preferably 420°C-480°C, more preferably 440°C-460°C, and most preferably 450°C; the time of the carbon coating is preferably 1-3 h, more preferably 1.5-2.5 h, and more preferably 2 h; the heating rate of the carbon coating is preferably 3-7°C / min.

[0041] The carbon-coated coal powder is subjected to high-temperature carbonization in a protective atmosphere to obtain a carbon material; the protective atmosphere can be any protective atmosphere familiar to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of argon, helium, neon, krypton, xenon and radon; the temperature of the high-temperature carbonization is preferably 1000°C to 1500°C, more preferably 1200°C to 1500°C, more preferably 1200°C to 1400°C, and most preferably 1300°C; the time of the high-temperature carbonization (i.e., the insulation time) is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and more preferably 2 hours; the heating rate of the high-temperature carbonization is preferably 1 to 10°C / min.

[0042] The present invention also provides a carbon material prepared by the above preparation method.

[0043] The present invention also provides a negative electrode material for a sodium ion battery, comprising the carbon material prepared by the above preparation method.

[0044] The present invention also provides a sodium ion battery, comprising the above-mentioned negative electrode material for a sodium ion battery.

[0045] More specifically, the sodium ion battery includes a negative electrode, and the negative electrode includes a negative electrode active layer; the negative electrode active layer includes the above-mentioned negative electrode material for the sodium ion battery, a conductive agent and a binder; the mass of the negative electrode material for the sodium ion battery is preferably 80% to 95% of the negative electrode active mass, more preferably 80% to 90%, and even more preferably 80% to 85%.

[0046] In order to further illustrate the present invention, a carbon negative electrode material and a preparation method thereof, and a sodium ion battery provided by the present invention are described in detail below in conjunction with embodiments.

[0047] The reagents used in the following examples are all commercially available; the anthracite used in the examples is No. 3 anthracite; the asphalt is coal tar asphalt; and the model of the commercial glass fiber used in the examples is GF / B GMF Circles.

[0048] Example 1

[0049] Step 1: Wash the anthracite with a mixed acid solution (5 mol / L hydrochloric acid, 10 wt.% hydrofluoric acid) to remove impurities, and then wash repeatedly with deionized water to obtain anthracite free of impurities.

[0050] Step 2: Add the anthracite and asphalt from which impurities have been removed into a ball mill at a mass ratio of 20:1 and mill for 20 hours to obtain asphalt-coated coal powder with a particle size of 500 mesh after ball milling.

[0051] Step 3: pre-carbonize the asphalt-coated coal powder after ball milling in step 2 at 450° C. for 2 hours to obtain coated pyrolysis coal powder.

[0052] Step 4: Place the coated pyrolyzed coal powder in step 3 under acetylene atmosphere at a flow rate of 200 mL min -1 , carbon deposition is carried out at 450°C for 2 hours to obtain deposited coal powder.

[0053] Step 5: The deposited coal powder obtained in step 4 is subjected to high-temperature carbonization in an argon atmosphere at a carbonization temperature of 1300° C. for a carbonization time of 2 h to obtain a carbon material with a yield of 89%.

[0054] The carbon material obtained in Example 1 was analyzed using a scanning electron microscope, and its scanning electron microscope image was obtained as follows: Figure 1 As shown, a is the SEM image of the carbon material at 1K magnification, b is the SEM image of the carbon material at 3K magnification, and c is the SEM image of the carbon material at 5K magnification.

[0055] The carbon material obtained in Example 1 was analyzed by X-ray diffraction, and its XRD pattern was as follows: Figure 2 shown.

[0056] The carbon material was mixed with the conductive agent Super P and CMC (80:10:10) and then the slurry was evenly coated on the aluminum foil (1.3 mg / cm 2 ), weigh the tablets, and in a glove box, use a metal sodium sheet as the counter electrode, commercial glass fiber as the diaphragm, and 1 mol / L electrolyte (solute is NaClO 4, solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1), the battery assembly order is: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → spring → negative electrode shell assembly battery, and then use a sealing machine to seal the battery. Finally, let it stand at room temperature for 12 hours to prepare for the test of electrochemical performance, and its cycle performance diagram is as follows Figure 3 When the charge and discharge cycle is carried out at a rate of 0.1C between 0.005 and 3V, its first coulombic efficiency can reach 84%, the first discharge capacity is 304mAh / g, and the capacity retention rate after 50 cycles is 76.3%.

[0057] Example 2

[0058] Step 1: Wash the anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, and then wash repeatedly with deionized water to obtain anthracite free of impurities.

[0059] Step 2: Add the anthracite with impurities removed and the phenolic resin into a ball mill at a mass ratio of 20:1 and mill for 20 hours to obtain a phenolic resin-coated coal powder with a particle size of 500 meshes.

[0060] Step 3: pre-carbonize the phenolic resin coated coal powder after ball milling in step 2 at 450° C. for 2 hours to obtain coated pyrolysis coal powder.

[0061] Step 4: Place the coated pyrolyzed coal powder in step 3 under acetylene atmosphere at a flow rate of 200 mL min -1 , carbon deposition is carried out at 450°C for 2 hours to obtain deposited coal powder.

[0062] Step 5: The deposited coal powder obtained in step 4 is subjected to high-temperature carbonization in an argon atmosphere at a carbonization temperature of 1300° C. for a carbonization time of 2 h to obtain a carbon material with a yield of 83%.

[0063] The carbon material was mixed with the conductive agent Super P and CMC (80:10:10) and then the slurry was evenly coated on the aluminum foil (1.3 mg / cm 2 ), weigh the tablets, and in a glove box, use a metal sodium sheet as the counter electrode, commercial glass fiber as the diaphragm, and 1 mol / L electrolyte (solute is NaClO 4 , solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1), the battery assembly order is: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → spring → negative electrode shell assembly battery, and then use a sealing machine to seal the battery. Finally, let it stand at room temperature for 12 hours to prepare for the test of electrochemical performance, and its cycle performance diagram is as follows Figure 4When the charge and discharge cycle is carried out at a rate of 0.1C between 0.005 and 3V, its first coulombic efficiency can reach 80%, the first discharge capacity is 340mAh / g, and the capacity retention rate is 74% after 50 cycles.

[0064] Example 3

[0065] Step 1: Wash the anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, and then wash repeatedly with deionized water to obtain anthracite free of impurities.

[0066] Step 2: Add the anthracite and cellulose from which impurities have been removed into a ball mill at a mass ratio of 20:1 and mill for 20 hours to obtain a cellulose-coated coal powder with a particle size of 500 meshes.

[0067] Step 3: pre-carbonize the cellulose-coated coal powder after ball milling in step 2 at 450° C. for 2 hours to obtain coated pyrolysis coal powder.

[0068] Step 4: Place the coated pyrolyzed coal powder in step 3 under acetylene atmosphere at a flow rate of 200 mL min -1 , carbon deposition is carried out at 450°C for 2 hours to obtain deposited coal powder.

[0069] Step 5: The deposited coal powder obtained in step 4 is subjected to high-temperature carbonization in an argon atmosphere at a carbonization temperature of 1300° C. for a carbonization time of 2 h to obtain a carbon material with a yield of 88%.

[0070] The carbon material was mixed with the conductive agent Super P and CMC (80:10:10) and then the slurry was evenly coated on the aluminum foil (1.3 mg / cm 2 ), weigh the tablets, and in a glove box, use a metal sodium sheet as the counter electrode, commercial glass fiber as the diaphragm, and 1 mol / L electrolyte (solute is NaClO 4 , solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1), the battery assembly order is: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → spring → negative electrode shell assembly battery, and then use a sealing machine to seal the battery. Finally, let it stand at room temperature for 12 hours to prepare for the test of electrochemical performance, and its cycle performance diagram is as follows Figure 5 When the charge and discharge cycle is carried out at a rate of 0.1C between 0.005 and 3V, its first coulombic efficiency can reach 86%, the first discharge capacity is 325mAh / g, and the capacity retention rate is 72% after 50 cycles.

[0071] It can be seen from Examples 1 to 3 that by coating anthracite, the surface defects of the anthracite can be reduced, thereby improving the first coulombic efficiency of the anthracite hard carbon.

[0072] Example 4

[0073] Step 1, washing the anthracite with a mixed acid solution (5 mol / L hydrochloric acid, 10 wt.% hydrofluoric acid) to remove impurities, and then repeatedly washing with deionized water to obtain anthracite free of impurities;

[0074] Step 2: Add the anthracite obtained in step 1 and remove impurities into a ball mill and mill for 20 hours to obtain coal powder with a particle size of 500 mesh.

[0075] Step 3: The ball-milled coal powder in step 2 is placed in an acetylene atmosphere at a flow rate of 200 mL min -1 , carbon deposition was carried out at 450°C and the carbon deposition time was 2h.

[0076] Step 4: The acetylene carbon-coated coal powder prepared in step 3 is subjected to high-temperature carbonization in an argon atmosphere at a carbonization temperature of 1300° C. for a carbonization time of 2 h to obtain a carbon material with a yield of 89%.

[0077] The carbon material was mixed with the conductive agent Super P and CMC (80:10:10) and then the slurry was evenly coated on the aluminum foil (1.3 mg / cm 2 ), weigh the tablets, and in a glove box, use a metal sodium sheet as the counter electrode, commercial glass fiber as the diaphragm, and 1 mol / L electrolyte (solute is NaClO 4 , solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1), the battery assembly order is: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → spring → negative electrode shell assembly battery, and then use a sealing machine to seal the battery. Finally, let it stand at room temperature for 12 hours to prepare for the test of electrochemical performance, and its cycle performance diagram is as follows Figure 6 The charge and discharge cycles were performed between 0.005-3V at a rate of 0.1C.

[0078] Example 5

[0079] The conditions of Example 3 were followed, except that different hydrocarbon atmospheres were used to prepare hard carbon materials. The performance of anthracite carbon materials prepared by carbon deposition in different hydrocarbon atmospheres in sodium ion batteries was investigated, and the results are shown in Table 1.

[0080] Table 1 Performance comparison of anthracite carbon materials prepared by carbon deposition in different hydrocarbon atmospheres in sodium ion batteries

[0081]

[0082] Different carbon coating methods have a great impact on the performance of anthracite hard carbon. Asphalt, phenolic resin, and cellulose coated anthracite hard carbon show higher capacity, but cellulose coated anthracite shows better electrochemical performance after acetylene deposition. Hydrocarbon gas will decompose at high temperature to produce carbon free radicals, which will gradually deposit on the surface of anthracite. Because small molecular gases will volatilize during the pyrolysis of anthracite, a large number of voids and defects will be formed, and these carbon free radicals will be deposited in these voids, which can control the specific surface area and reduce the effect of surface defects. Therefore, hydrocarbon gas can greatly improve the first coulomb efficiency of anthracite hard carbon. However, the carbon free radicals produced by the cracking of different hydrocarbons are quite different. The deposited carbon particle size produced by the cracking of hydrocarbons with larger molecular weight is larger, which has poor filling effect on the surface voids of anthracite and poor coating effect on anthracite hard carbon. On the whole, acetylene has the best effect as a coated carbon source.

[0083] Comparative Example 1

[0084] Step 1: Wash the anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, and then wash repeatedly with deionized water to obtain anthracite free of impurities.

[0085] Step 2: Add the anthracite from which impurities have been removed in step 1) into a ball mill and mill for 20 hours to obtain a coal powder with a particle size of 500 meshes.

[0086] Step 3: The coal powder prepared in step 2 is subjected to high-temperature carbonization in an argon atmosphere, the carbonization temperature is 1300° C., the carbonization time is 2 h, and a carbon material is obtained with a yield of 71%.

[0087] The carbon material was mixed with the conductive agent Super P and CMC (80:10:10) and then the slurry was evenly coated on the aluminum foil (1.3 mg / cm 2 ), weigh the tablets, and in a glove box, use a metal sodium sheet as the counter electrode, commercial glass fiber as the diaphragm, and 1 mol / L electrolyte (solute is NaClO 4 , solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1), the battery assembly order is: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → spring → negative electrode shell assembly battery, and then use a sealing machine to seal the battery. Finally, let it stand at room temperature for 12 hours to prepare for the test of electrochemical performance, and its cycle performance diagram is as follows Figure 7 The charge and discharge cycle was carried out at a rate of 0.1C between 0.005-3V, and its first coulombic efficiency was 72%, the first discharge capacity was 250mAh / g, and the capacity retention rate was 50% after 50 cycles.

[0088] Comparative Example 2

[0089] Step 1: Wash the anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, and then wash repeatedly with deionized water to obtain anthracite free of impurities.

[0090] Step 2: Add the anthracite from which impurities have been removed in step 1 and cellulose in a mass ratio of 20:1 into a ball mill and mill for 20 hours to obtain a cellulose-coated coal powder with a particle size of 500 meshes after ball milling.

[0091] Step 3: pre-carbonize the cellulose-coated coal powder after ball milling in step 2 at 450° C. for 2 hours to obtain coated pyrolysis coal powder.

[0092] Step 4: The coated pyrolysis coal powder in step 3 is subjected to high-temperature carbonization in an argon atmosphere at a carbonization temperature of 1300° C. for a carbonization time of 2 h to obtain a carbon material with a yield of 85%.

[0093] The carbon material was mixed with the conductive agent Super P and CMC (80:10:10) and then the slurry was evenly coated on the aluminum foil (1.3 mg / cm 2 ), weigh the tablets, and in a glove box, use a metal sodium sheet as the counter electrode, commercial glass fiber as the diaphragm, and 1 mol / L electrolyte (solute is NaClO 4 , solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1), the battery assembly order is: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → spring → negative electrode shell assembly battery, and then use a sealing machine to seal the battery. Finally, let it stand at room temperature for 12 hours to prepare for the test of electrochemical performance, and its cycle performance diagram is as follows Figure 8 The charge and discharge cycle was carried out at a rate of 0.1C between 0.005 and 3V, and its first coulombic efficiency was 72%, the first discharge capacity was 250mAh / g, and the capacity retention rate was 50% after 50 cycles.

[0094] It can be seen from Comparative Examples 1 and 2 that the directly carbonized anthracite has more surface defects, a large number of macropores, and a low residual carbon rate, indicating that the volatile matter is more serious, resulting in a low first coulombic efficiency and a low capacity of the sodium ion battery, which cannot meet the practical application of the sodium ion battery.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon material, characterized in that: The following steps are involved: S1) subjecting anthracite to a de-impurity treatment to obtain anthracite free of impurities; S2) grinding the anthracite from which impurities have been removed to obtain ground anthracite; S3) introducing hydrocarbon gas into the ground anthracite in a protective atmosphere to perform carbon coating by chemical vapor deposition to obtain carbon-coated coal powder; S4) carbonizing the carbon-coated coal powder at high temperature in a protective atmosphere to obtain a carbon material.

2. The preparation method according to claim 1, characterized in that: In the step S2), an organic carbon source is added during grinding, and then pyrolysis is performed to obtain ground anthracite.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the anthracite from which impurities have been removed to the organic carbon source is 20:(0.5-2).

4. The preparation method according to claim 2, characterized in that: The anthracite is selected from No. 3 anthracite; The organic carbon source is selected from one or more of asphalt, phenolic resin and cellulose; And / or, the protective atmosphere is selected from one or more of argon, helium, neon, krypton, xenon and radon; And / or, the hydrocarbon gas is selected from one or more of methane, acetylene, ethylene, propane and natural gas.

5. The preparation method according to claim 2, characterized in that: The pyrolysis temperature in step S2) is 400°C to 500°C; the pyrolysis time is 1 to 3 hours; and the heating rate of the pyrolysis is 1 to 10°C / min.

6. The preparation method according to claim 1, characterized in that: In the step S3), the temperature of the carbon coating is 400° C. to 500° C.; the time of the carbon coating is 1 to 3 hours; and the heating rate of the carbon coating is 3 to 7° C. / min.

7. The preparation method according to claim 1, characterized in that: The volume ratio of the protective atmosphere to the hydrocarbon gas is 5:(0.5-2); the flow rate of the hydrocarbon gas is 150-250 mL / min.

8. The preparation method according to claim 1, characterized in that: The temperature of the high-temperature carbonization in step S4) is 1000°C to 1500°C; the time of the high-temperature carbonization is 1 to 3 hours; and the heating rate of the high-temperature carbonization is 1 to 10°C / min.

9. A negative electrode material for a sodium ion battery, characterized in that: The invention comprises a carbon material prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: Including the negative electrode material for sodium ion battery according to claim 9.

Citation Information

Patent Citations

  • Preparation method of anthracite-based hard carbon material combining pre-activation pore-forming and high-temperature carbonization

    CN112645305A

  • Preparation method and application of coal-based functional carbon material

    CN117623274A

  • Negative electrode material, method for producing the same, negative electrode, and battery comprising the same

    WO2014032595A1